We have to solve sin 2t - 3 = 6 sin t - cos t for x.

Now sin 2t = 2 sin t cos t

sin 2t - 3 = 6 sin t- cos t

=> 2sin t *cos t -3 = 6 sin t - cos t

=> 2sin t *cos t - 6 sin t + cos t - 3 = 0

=> 2 sin t( cost - 3) +1 ( cos t - 3) = 0

=> ( 2 sin t +2) ( cos t -3) = 0

For 2 sin t + 2 = 0

=> sin t = -2/2 = -1

=> t = arc sin (-1)= -90 degree

For cos t -3 =0, we don't have any value of t as cos t > 1.

**Therefore t = -90 degrees.**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now